La relation entre accord et concordance dans deux dialectes des Grisons (Atti del Sodalizio Glottologico Milanese, 2021)
This article deals with the agreement system of two dialects spoken in southern Switzerland. In both, FPL agreement is marked by the suffix -n, which is a reflex of the 6th person verbal ending. In Bregagliotto, the more conservative dialect of the two, -n occurs in the second position of FPL NPS (FPL and FSG NPs are otherwise identical). In Mesolcinese, -n occurs on all inflected elements that agree with a feminine plural controller (including finite verbs), except definite articles and subject clitics.
Keywords: Agreement; Concordance; Italo-Romance; Dialects; Reanalysis